Asociația Națională A Fabricanților De Produse de Uz Veterinar - Date sintetice privind statusul farmaciilor veterinare din România în 2025 - Nistor Maierean (Medicamentul Veterinar, 2025)
The results of the questionnaire regarding the application of the requirements of ANSVSA Ordinance no. 83/2014 with subsequent amendments and additions 05.2024, are presented synthetically.